Object-oriented Python : master OOP by building games and GUIs - Kalb, Irv (No Starch Press, 2022)
"This guide to mastering object-oriented programming with Python covers the basics of building classes and creating objects through clear examples using the pygame package. Also explores key concepts like encapsulation, polymorphism, and inheritance as well as best practices for coding with objects"--